(untitled) (Journal of The Colloquium for Information Systems Security Education, 2016)
Malicious insiders continue to post great threats to organizations. With their knowledge about organization and access to organizational resources, malicious insiders could bypass security countermeasures easily and result in devastating consequences. In this study we compare 30 malicious insiders with 30 benign insiders with respect to the personality and other psychometrics. We found that avoidant personality, antisocial personality and disruptive mood differentiate malicious insiders with the benign ones. Also, if an insider is both narcissistic and disgruntled, he/she tends to launch the malicious attack. The implication for this research has two aspects: first, we validated the characteristics of malicious insiders proposed by previous research, second, the findings suggest that organizations should be more sensitive to employees who exhibit certain behavioral precursors.